2007
DOI: 10.1080/01676830701558091
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Magnetic Resonance Imaging of the Upper Eyelid: Correlation with the Position of the Skin Crease in the Upper Eyelid

Abstract: MRI provides excellent images and allows a good analysis of the upper eyelid components. It permits a detailed analysis of the architecture for a better understanding of its appearance and of the crease position, although further investigation with a larger number of volunteers is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Overriding of the preseptal over the pretarsal OOM has not been the focus in previous MRI studies of the eyelid 16,17. Therefore even though some MRI scans of Asian eyelids in the literature16 showed overriding preseptal OOM, the finding was not reported.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Overriding of the preseptal over the pretarsal OOM has not been the focus in previous MRI studies of the eyelid 16,17. Therefore even though some MRI scans of Asian eyelids in the literature16 showed overriding preseptal OOM, the finding was not reported.…”
Section: Discussionmentioning
confidence: 93%
“…None of the eyelids in this study demonstrated entropion even though cadaveric eyelid tends to loosen horizontally secondary to loss of basal muscular tone 14. For Caucasian lower eyelids, there has been no microscopic cadaveric studies,15 magnetic resonance imaging (MRI), or any other imaging studies16,17 done for overriding of preseptal OOM. In addition, previous imaging or microscopic cadaveric studies in the upper eyelid were not focused on the overriding of the preseptal OOM on the pretarsal part, and overriding has not been identified as a causative factor of involutional upper eyelid entropion 18…”
mentioning
confidence: 84%
“…4,7,14 The fusional part of the orbital septum and levator aponeurosis in Caucasian double eyelid is typically in the skin crease. 15 In a Japanese double eyelid with no drooping of preaponeurotic fat pad and/or suborbicularis fibroadipose tissue, the skin crease was also at this fusional point (5/17, 29.4%). In 4 single eyelid specimens there was no drooping of preaponeurotic fat pad and/ or suborbicularis fibroadipose tissue, possibly due to factors related to the thickness of the orbicularis muscle, although the levator aponeurosis extension was present in all of them.…”
Section: Discussionmentioning
confidence: 95%
“…All statistical analysis was carried out using the Dr. SPSS II for Windows software (SPSS Japan Inc., Tokyo, Japan). In the eyelid margin area, all fibers of the aponeurosis followed an antero-oblique course between the pretarsal orbicularis oculi muscle and the muscle of Riolan, 15 Spacing Between Orbicularis Oculi Muscle Bundles. In 7 specimens with a double eyelid, the spacing between orbicularis bundles was tight (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Facial volume measurements have recently been described using ultrasound, computed tomography (CT), as well as magnetic resonance imaging (MRI) analysis. [8][9][10][11][12] The ability of MRI to distinguish fat from other soft tissues makes it a particularly useful modality to evaluate the MFP. 13 The earliest techniques of facial rejuvenation have been continuously adapted to reflect changes in the understanding of the aging face.…”
mentioning
confidence: 99%